Poets of Hope and Despair The Russian Symbolists in War and Revolution, 1914-1918 - Hellman, Ben (Russian History and Culture, 2018)
an account of the response of the Russian Symbolist poets to the Great War and the Russian revolutions of 1917. Readership: All interested in Russian modernism, especially Symbolism, and Russian history of the war years 1914-1918 and the revolutions of 1917.